Electrical characterization and examination of temperature-induced degradation of metastable Ge0.81Sn0.19 nanowires. Issue 41 (12th October 2018) - Sistani, M.; Seifner, M. S.; Bartmann, M. G.; Smoliner, J.; Lugstein, A.; Barth, S.
Abstract : Electrical characterization of Ge0.81 Sn0.19 nanowires has been performed revealing high electrical conductivity and semiconductor behaviour when cooled to 10 K. The impact on slightly elevated temperatures on the device stability of this metastable material is described. Abstract : Metastable germanium–tin alloys are promising materials for optoelectronics and optics. Here we present the first electrical characterization of highly crystalline Ge0.81 Sn0.19 nanowires grown in a solution-based process. The investigated Ge0.81 Sn0.19 nanowires reveal ohmic behavior with resistivity of the nanowire material in the range of ∼1 × 10 −4 Ω m. The temperature-dependent resistivity measurements demonstrate the semiconducting behavior. Moreover, failure of devices upon heating to moderate temperatures initiating material degradation has been investigated to illustrate that characterization and device operation of these highly metastable materials have to be carefully conducted.